Latin America and the historiography of international criminal law - Quintana, Francisco José (Universidad Nacional del Litoral, 2020)
This article explores the relationship between the history of international criminal law, the historical turn in international law, and Latin America. The article argues that the «textbook narrative» has facilitated the justification of the project of international criminal law at the expense of spreading a simplistic history that assumes that the discipline has existed in its actual form since, at least, the aftermath of World War II. The article shows how this narrative has begun to be challenged by the historical turn in international law, which has instilled a methodological concern to international legal scholarship broadly. Finally, this article argues that the exclusion of certain developments that took place in Latin America during the transitions to democracy starting in the 1980s from the conventional history of international criminal law points to a number of significative problems in the historiography of the discipline.